Novel Delay-Decomposing Approaches to Absolute Stability Criteria for Neutral-Type Lur'e Systems. (2nd December 2019) - Guo, Liang-Dong; Huang, Sheng-Juan; Wu, Li-Bing
Abstract : The problem of absolute stability analysis for neutral-type Lur'e systems with time-varying delays is investigated. Novel delay-decomposing approaches are proposed to divide the variation interval of the delay into three unequal subintervals. Some new augment Lyapunov–Krasovskii functionals (LKFs) are defined on the obtained subintervals. The integral inequality method and the reciprocally convex technique are utilized to deal with the derivative of the LKFs. Several improved delay-dependent criteria are derived in terms of the linear matrix inequalities (LMIs). Compared with some previous criteria, the proposed ones give the results with less conservatism and lower numerical complexity. Two numerical examples are included to illustrate the effectiveness and the improvement of the proposed method.